Electron Transport Through Photosystem II Is Not Limited By A Wide Range of Water Deficit Conditions In Field‐Grown Gossypium hirsutum. Issue 1 (26th November 2013) - Snider, J. L.; Collins, G. D.; Whitaker, J.; Perry, C. D.; Chastain, D. R.
Abstract Despite exhaustive literature describing drought stress effects on photosynthesis in Gossypium hirsutum, the sensitivity of photosynthetic electron flow to water deficit is heavily debated. To address this, G. hirsutum plants were grown at a field site near Camilla, GA under contrasting irrigation regimes, and pre‐dawn water potential (ΨPD), stomatal conductance (gs), net photosynthesis (PN), actual quantum yield of photosystem II (ΦPSII) and electron transport rate (ETR) were measured at multiple times during the 2012 growing season. ΨPD values ranged from −0.3 to −1.1 MPa. Stomatal conductance exhibited a strong (r2 = 0.697), sigmoidal response to ΨPD, where gs was ≤0.1 mol m−2 s−1 at ΨPD values ≤ −0.86 MPa. Neither ΦPSII (r2 = 0.015) nor ETR (r2 = 0.010) was affected by ΨPD, despite exceptionally low ΨPD values (−1.1 MPa) causing a 71.7 % decline in PN relative to values predicted for well‐watered G. hirsutum leaves at ΨPD = −0.3 MPa. Further, PN was strongly influenced by gs, whereas ETR and ΦPSII were not. We conclude that photosynthetic electron flow through photosystem II is insensitive to water deficit in field‐grown G. hirsutum.